2019
DOI: 10.21660/2019.55.76923
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anionic Components of Lead on Biotoxicity and Bioaccumulation Ability in Respect of Probiotic Stamps

Abstract: Lead is one of the most dangerous xenobiotic elements. It is actively accumulated not only in the environment, the distribution of lead in the water-soil-plant-animal-man chain directly depends on the initial content of elements in the geochemical province and is directly related to the health of the population.[1]. This paper presents the results of a study of the biotoxicity of lead cations in the structure of salts with different anionic components in relation to bacteria of the genus Bacillus, which are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Several methods are available to mitigate heavy metal contamination in aqueous solutions, including electrolysis, oxidation–reduction, and membrane separation. However, many of these methods have high operating costs and low separation efficiencies in wastewater with a low lead content. Therefore, adsorbent separation processes have attracted the attention of researchers because of their relatively simple operational processes, low potential for byproduct formation, low cost, and easy regeneration procedures. , Many adsorbents have been synthesized from activated carbon, , biomaterials, , and zeolites. Among the many adsorbents, zeolite has good adsorption properties due to its high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods are available to mitigate heavy metal contamination in aqueous solutions, including electrolysis, oxidation–reduction, and membrane separation. However, many of these methods have high operating costs and low separation efficiencies in wastewater with a low lead content. Therefore, adsorbent separation processes have attracted the attention of researchers because of their relatively simple operational processes, low potential for byproduct formation, low cost, and easy regeneration procedures. , Many adsorbents have been synthesized from activated carbon, , biomaterials, , and zeolites. Among the many adsorbents, zeolite has good adsorption properties due to its high specific surface area.…”
Section: Introductionmentioning
confidence: 99%
“…For many microorganisms, the effectiveness of biological detoxification of metals through targeted microbial activity depends on factors such as the age of culture, the cell shape, pH, contact time, and initial concentrations of metals in the solution [6]. In this regard, several studies with actively growing cells showed that some microorganisms could effectively remove heavy metal ions from the nutrient environment, especially when the concentration of metals was relatively low [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, works discussing the problems and new possibilities of using synthetic preparations and natural substances in the diet of farm animals have appeared. A broad class of antibiotics, extracts, and preparations obtained from oak bark [9][10][11] can be considered as an example of combined use. The aim was to study the combined use of chlortetracycline and Quercus cortex extract.…”
Section: Introductionmentioning
confidence: 99%